2016
DOI: 10.3747/co.23.3399
|View full text |Cite
|
Sign up to set email alerts
|

Annual Surveillance Mammography After Early-Stage Breast Cancer and Breast Cancer Mortality

Abstract: Background After treatment for early-stage breast cancer (bca), annual surveillance mammography (asm) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…This is mainly because the benefit of annual routine surveillance is still debatable given the many disadvantages regarding false positives, recall rates and increasing the psychological burden on patients, and individual risk predictions are not widely utilised in clinical practice. Despite the guideline recommendation for annual mammography and strong consensus between many different practice guidelines, this routine surveillance is not evidence-based but rather on the assumption that early detection of recurrence reduces breast cancer mortality [ 36 , 37 ]. Furthermore, evidence of other surveillance intervals or the efficacy of different imaging modalities is lacking, whilst clinical practice is calling for personalised follow-up based on risk and patients’ needs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly because the benefit of annual routine surveillance is still debatable given the many disadvantages regarding false positives, recall rates and increasing the psychological burden on patients, and individual risk predictions are not widely utilised in clinical practice. Despite the guideline recommendation for annual mammography and strong consensus between many different practice guidelines, this routine surveillance is not evidence-based but rather on the assumption that early detection of recurrence reduces breast cancer mortality [ 36 , 37 ]. Furthermore, evidence of other surveillance intervals or the efficacy of different imaging modalities is lacking, whilst clinical practice is calling for personalised follow-up based on risk and patients’ needs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…By improving mammographic experiences for patients, it is hoped that uptake will increase translating into earlier diagnosis and increased survival. 14,15 Additionally, it is an important healthcare priority to reduce nonattendance rates in terms of cost savings and time. 16 This study compared previous and current mammography examinations and data showed that there was strong correlation of pain between the two time points (r ¼ 0.79, P < 0.001, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We adhered to Statistics Canada's recommendation not to report income quintiles in rural areas, owing to the variation of income within a single rural postal code, an approach that has been adopted by past studies. [25][26][27][28] Using the OHIP database, we identified all primary care physician and long-term follow-up clinic visits in the year before the start date of each surveillance lookback period. We categorized Johns Hopkins' Aggregated Diagnosis Groups (ADG) scores, representing measures of morbidity, 29,30 as none, low (1-5), intermediate (6)(7)(8)(9), and high (≥ 10).…”
Section: Data Sourcesmentioning
confidence: 99%